Dual roles of in situ generated HSP70 in antigen delivery and immunoregulation - Kang, Xinliang; Li, Zhuofan; Nakkala, Jayachandra Reddy; Li, Yibo; Akter, Labone; Zhao, Yiwen; Chen, Xinyuan (Frontiers in Immunology, 2025)
IntroductionExtracellular release of inducible HSP70 spurred interests to explore its potential interactions with innate immune systems. Both pro- and anti-inflammatory roles have been reported though the immunostimulatory roles were largely disputed due to the likely use of contaminated HSP70. The anti-inflammatory roles inspired the exploration of HSP70 to treat autoimmune diseases by suppressing pathological inflammatory responses. Besides immunomodulation, HSP70 has been explored as tumor vaccine carriers to elicit cytotoxic T lymphocyte responses due to its ability to deliver bound peptides to MHC I presentation pathway. With increasing understanding of the potential use of ex vivo prepared HSP70 in vaccination and therapy, the functions and potential applications of in situ induced HSP70 in antigen delivery and immunomodulation remain largely unexplored.MethodsThis study utilizes physical radiofrequency adjuvant (RFA) to induce HSP70 synthesis accompanied with mild inflammation followed by intradermal injection of vaccine antigens into RFA-treated skin in murine models to explore its potential roles in antigen delivery and immunomodulation.ResultsWe found in situ induced HSP70 could bind intradermally injected model antigen ovalbumin and contribute to enhanced antigen uptake in skin and draining lymph nodes. HSP70 failed to induce dendritic cell maturation and rather suppressed RFA-induced TLR4/IRAK/NFκB activation and IL-6 expression.DiscussionThese results indicate dual roles of in situ induced HSP70 in antigen delivery and immunoregulation at physiological conditions. These dual functions highlight opportunities to exploit endogenous HSP70 for both vaccine adjuvantation and immunomodulation.